[PP.17.24] THE RESPONSE OF PLASMA ALDOSTERONE TO SALINE INFUSION IS UNDER THE INFLUENCE OF AGE IN PRIMARY HYPERTENSION. (September 2017) - Catena, C.; Colussi, G.L.; Novello, M.; Bertin, N.; Sechi, L.A.
Abstract : Objective: In patients with primary hypertension, plasma aldosterone (PA) levels are significantly decreased by an intravenous saline load (IVSL), but this response is variable among patients and related to the ability of salt to modulate aldosterone production. Previous studies have reported that the activity of the renin-angiotensin-aldosterone system is related with age. The aim of this study was to investigate whether age might affect the aldosterone response to an IVSL. Design and method: In 124 hypertensive patients (48 ± 13 y, 71 males) who were washed-out of antihypertensive drugs for 2 weeks, we measured renin and PA levels before and after an IVSL (2 lt. saline in 4 h). In all patients secondary causes of hypertension were excluded. For statistical purposes patients were subdivided into two groups based on age (< or > 60 y). Results: Twenty-three of 124 patients (18%) were had 60 y of age or more (range 61–77) and the remaining were younger than 60 y (19–60 y). No differences were found between the two groups for gender, body mass index, serum potassium and creatinine clearance. Urinary sodium excretion was comparable in patients older (159 ± 83) or younger (159 ± 66) than 60 y. Baseline PA (76 [49–121] pg/ml) and renin (5.0 [1.9–9.8] mcIU/ml) levels were significantly lower in patients older than 60 y than in those younger than 60 y (115 [77–162] pg/ml, P = 0.019; 10.7 [5.1–20.8] mcIU/ml, P = 0.026). As expected IVSL decreased significantly (P < 0.001) both plasma renin and aldosterone levels. Post IVSL renin was 3.0 [1.1–4.9] mcIU/ml in patients older than 60 y and 6.2 [3.0–12.5] mcIU/ml younger than 60 y. Following IVSL, PA decreased by 87% (10 [10–13] pg/ml) in patients older than 60 y and by 76% (28 [10–49] pg/ml; P = 0.003) in patients younger than 60 y. The change in PA induced by IVSL was significantly and inversely related to age (r = -0.185, P = 0.039). Conclusions: PA levels are lower in hypertensive patients older than 60 y. This difference becomes more relevant after IVSL suggesting greater response of the renin-angiotensin system to volume expansion. This should be taken into account in the diagnostic work-up of hypertensive patients.